Estimation on real carrying capacity for Mini Irau Trail, Cameron Highland, Pahang - Umar, Muhammad Naufal (2019)
Nowadays, consumer engagement in mountain-climbing activities in Malaysia has been increasing especially among the youths. Despite of many challenges, experiences and fun the climbers would got, there are some part that they unaware of the various damage or impacts that occur in the forest trails. Among the major impacts that can be seen and occurred are the impact on the soil and vegetation along the mountain trail. Uncontrolled climbers are also one of the main causes of the trail having a negative impact. This study was conducted to identify real and social carrying capacity estimates by Mini Irau trail climbers at Mossy Forest, Cameron Highland, Pahang. The method used in this study was rapid survey technique and quantitative descriptive method. Overall, the results obtained from this study found that the trail at Mini Irau was in poor condition. The number of climbers who cannot be controlled even though permits are only allowed for a certain amount resulting in trails of the Mount Irau decreased in quality compared to the previous. The management should take firm action by setting the number of permits to the user of this mountain based on the amount of carrying capacity that has been reviewed and puts the guard at the entrance of the route to Mossy Forest. In addition, this Mini Irau trail must also be closed at certain times as in the monsoon season to enable it to be restored naturally. Finally, with this kind of research, the Pahang Forestry Department could designed a program that should be held with locals, nature guides, mountain climbers and the citizen to minimize the impact on the trail and preserve the resources in Malaysia.